Clinical and bacteriological evaluation of adapalene 0.1% gel plus nadifloxacin 1% cream versus adapalene 0.1% gel in patients with acne vulgaris. Issue 8 (3rd June 2013) - Takigawa, Masahiro; Tokura, Yoshiki; Shimada, Shinji; Furukawa, Fukumi; Noguchi, Norihisa; Ito, Taisuke; ,
Abstract: This multicenter, randomized parallel group study investigated the efficacy and tolerability of adapalene 0.1% gel plus nadifloxacin 1% cream (combination therapy) compared with adapalene gel (monotherapy) during 12‐week treatment of acne vulgaris. A total of 184 Japanese patients aged above 12 years with moderate to severe acne as indicated by the Japanese severity grading criteria were randomized to combination therapy ( n = 84) and monotherapy ( n = 100) groups, both having comparable demographic and baseline characteristics. Adapalene was applied only to inflammatory acne lesions in order to minimize skin irritation and ensure the treatment results. Efficacy and safety evaluations, treatment compliance and satisfaction with drug application were periodically monitored. The combination therapy provided a significantly greater efficacy than adapalene in decrement of inflammatory papulopustular lesions at 4 weeks and thereafter ( P = 0.0056). The overall judgment of the therapeutic efficacy by the physician at the end of study revealed a significant difference ( P = 0.02496) between the groups in favor of combination therapy. Dryness was reported in a greater proportion of patients undergoing monotherapy than combination therapy at weeks 2 and 4 ( P = 0.04652). The patient self‐assessment in satisfaction with the drug application at the end of study revealed a significant difference ( P = 0.00268) between the groups in favor of combination therapy. Among 76 strains of Propionibacterium acnes isolated from 87 patients, no strain was resistant to nadifloxacin. Thus, the simultaneous use of adapalene and nadifloxacin may provide an additive and complementary effect, resulting in clinical superiority and greater patient adherence compared to adapalene monotherapy.